2022
DOI: 10.37335/ijek.v10i2.155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Attitude and Opportunity Recognition on Entrepreneurial Intention of University Students

Abstract: The study investigates the mediating role of entrepreneurial opportunity recognition on the relationship between entrepreneurial attitude and entrepreneurial intention among university students in Ghana. A structured questionnaire was administered to 500 university students in Ghana, and the data collected was analyzed using Amos. Structural equation modeling (SEM) was used to assess the hypothesized paths. The result indicated that entrepreneurial attitude had a substantial positive impact on both entrepreneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Finally, consistent with previous studies such as [3,28,29,31,34], this study's findings show that recognizing business opportunities positively affects entrepreneurial intentions and business startups. As highlighted by this study's findings, while Egyptian entrepreneurs have identified a need for more viable opportunities, the economic challenges and disruptions caused by the COVID-19 pandemic meant that they were hesitant to do so.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, consistent with previous studies such as [3,28,29,31,34], this study's findings show that recognizing business opportunities positively affects entrepreneurial intentions and business startups. As highlighted by this study's findings, while Egyptian entrepreneurs have identified a need for more viable opportunities, the economic challenges and disruptions caused by the COVID-19 pandemic meant that they were hesitant to do so.…”
Section: Discussionsupporting
confidence: 91%
“…The fear and anxiety about the COVID-19 pandemic causes adverse consequences regarding entrepreneurial intentions and, more specifically, the recognition of business opportunities [2,30]. Ledi et al's [31] findings demonstrate that recognizing business opportunities influences university students' entrepreneurial intentions and having an entrepreneurial mindset. When comparing the recognition of business opportunities based on gender and family business background, [32]'s findings offer insights to the demographic influences on identifying and seizing entrepreneurial possibilities.…”
Section: Business Opportunity Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various research studies from around the world seeking to quantify entrepreneurial intention have contributed to our understanding of EI over the past decades (Mares et al, 2016). The research conducted by Ledi et al, (2022) sheds light on the underlying mechanisms that drive entrepreneurial intention and self-employment propensity among university students in Ghana. The study found that cultivating an entrepreneurial mindset and developing a positive attitude towards entrepreneurship increases the likelihood of recognizing business opportunities and having the propensity for self-employment.…”
Section: Introductionmentioning
confidence: 99%
“…Such behaviors can destroy employee' morale, and be responsible for higher rates of absenteeism and lover turnover or productivity (Hoel et al, 2003). It can have negative influence on fundamental competitiveness factors such as internal and external entrepreneurship attitude, initiative potential or abilities to look for innovative solutions (see Dankiewicz et al, 2020;Skalická et al, 2023;Meluzín et al, 2018;Civelek et al, 2021;Ključnikov, et al 2021;Cortes, et al, 2021;Kuswanto et al, 2022;Ledi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%